Nitrate Removal Within Heterogeneous Riparian Aquifers Under Tidal Influence. Issue 10 (22nd May 2020) - Wallace, Corey D.; Sawyer, Audrey H.; Soltanian, Mohamad Reza; Barnes, Rebecca T.
Abstract: Tides in coastal rivers drive river‐groundwater (hyporheic) exchange and provide opportunities for nitrate removal that may improve coastal water quality. Silt and sand layers in coastal floodplain sediments can alter the flow and transformation of nitrate. Our goal was to understand how sediment heterogeneity influences nitrogen dynamics near tidal rivers. Numerical simulations show that oxic, variably saturated sand layers and anoxic, organic‐rich silt layers are sites of nitrification and denitrification, respectively. The exchange of river water and nitrate through heterogeneous sediments increases with sand fraction, as sand lenses become longer and more connected. The amount of nitrate removed from river water also increases but represents a smaller portion of total nitrate exchange through the hyporheic zone, causing removal efficiency to decline. Our results suggest that accurate characterization of aquifer heterogeneity leads to an improved understanding of sites of nutrient transformation within floodplain sediments. Plain Language Summary: Excess nitrate can degrade coastal water quality, but microbial reactions reduce its concentration within the bed and banks of tidal rivers, where surface water and groundwater mix. Spatial arrangements of different sediments (sand and mud) affect the mixing of river water and groundwater and thus affect nitrate removal. Here, we use computer models to simulate nitrate transformation along a tidal river with different amounts of coarse and fine sediments. Coarse sediments promote groundwater flow and nitrate production, while fine sediments promote nitrate removal. The amount of nitrate removed from river water is greater in aquifers with coarser sediments, but the removal efficiency decreases. Removal also varies with the spatial distribution of sand and mud in sediments but to a lesser degree. Computer models of nitrate transport should consider the distribution of different sediment types. Key Points: Tidal aquifers are a net sink of nitrate; removal magnitude varies with permeability structure Sediment organic matter is a local source of dissolved organic carbon driving small‐scale patterns of nitrate transformation Nitrification dominates in sand layers, where oxygen and nutrients are mobile; denitrification dominates in organic‐rich, silt layers